The effects of neighbours in plant communities: mathematical and experimental approaches - Fibich, Pavel (Jihočeská univerzita, 2012)
The effect of plant neighbourhood was investigating for hemiparasitic plants, productivity and diversity effects, constant final yield and recruits establishment. The research was based on a wide range of methods including the system of differential equations for population dynamic, individual based model with field of neighbourhood approach, glasshouse experiment and field experiment with gaps in the wet meadow.
The effects of neighbours in plant communities: mathematical and experimental approaches